INTRODUCTION OF CARBON DOPING INTO MOS2 AND ITS INFLUENCE ON THE OPTICAL AND ELECTRONIC PROPERTIES - Kiromil Enri Auni, Azrul
MoS is part of the transition metal dichalcogenides (TMDS) has unique properties like electronic and optical properties that it has great potential in various applications. MoSz modulation through the incorporation of dopant atoms allows changes in its properties, which in turn affects its optical performance. This research examines the electronic structure and optical properties of pure and carhon doped MOS2, directing it to the possible application. This research has been conducted using DFT and GW-BSE ap roach. The results show that the electronic structure of MoS modulated hy carbon doping varies not only affected by the dopant concentration hut also the position of the site. The dopant concentration of 12.5%•C carbon in MoSz gives rise to a high red-shift in the optical absor tion. The exciton also undergoes a red-shift for the 5.56%u do ant concentration, followed by the emergence of new exciton peaks at 0.83 eV. The 11.1% adatom doping system exhibits semicond LtCting behaviour, but the intensit y Of optical absorption is much lower than other systems. The optical performance of different doping concentration systems over a wider wavelength range opens up possible applications in optoelectronics, bioimaging and photothermal